The Effect of Auditor Competence and Skepticism on Remote Audit Quality - Mulyandani, Vina Citra (Indonesian Journal of Economics and Management, 2023)
This study aims to determine the effect of auditor competence and skepticism on remote audit quality. This type of research is descriptive quantitative. Respondents in this study were the Auditors of the Inspectorate General of the Ministry of Finance, totaling 82 people using probability sampling technique. Source of data in this research is primary data. Primary data was taken by distributing questionnaires and analyzed using multiple linear regression analysis after testing the validity, reliability, and classical assumption tests. Furthermore, the data was processed using the SPSS program application version 25.0. The results of this study show simultaneously and partially that auditor competence and skepticism have a positive and significant effect on remote audit quality. The results of the coefficient of determination simultaneously show that professional skepticism and auditor competence have a positive and significant effect on remote audit quality by 67.5%. The results of the regression coefficient show that partially professional skepticism has a positive and significant effect of 43.5%, auditor competence has a positive and significant effect of 57.2%. This means that professional skepticism and auditor competence together are very important for an auditor in maintaining the quality of his remote audit during the Covid-19 pandemic.